Anaerobic digestion of vinasse in fluidized bed reactors: Process robustness between two-stage thermophilic-thermophilic and thermophilic-mesophilic systems. (10th September 2021) - Ramos, Lucas Rodrigues; Lovato, Giovanna; Rodrigues, José Alberto Domingues; Silva, Edson Luiz
Abstract: Two-stage anaerobic digestion (AD) is a solution for the biodegradation of complex wastes, but the best association of temperatures between acidogenesis and methanogenesis is unclear. Our study investigated whether it is best to associate a thermophilic acidogenic reactor with a thermophilic or a mesophilic methanogenic reactor and results were compared to single-stage AD. The effect of increasing the organic loading rate (OLR from 2.7 to 24.7 kg COD/m 3 /d) in thermophilic and mesophilic second-stage methanogenesis of two-stage AD was also assessed. A thermophilic acidogenic reactor (R2-H2-Thermo ) treating sugarcane stillage fed thermophilic (R2-CH4-Thermo ) and mesophilic (R2-CH4-Meso ) methanogenic reactors. A single-stage methanogenic thermophilic reactor was used as control (R1-CH4-Thermo ). Reactors R2-CH4-Thermo and R2-CH4-Meso showed similar performance at OLR of 2.7–13.3 kg COD/m 3 /d, but the latter achieved the highest methane production rate at 24.7 kg COD/m 3 /d (3.2 L CH4 /d/L – 78% higher than R2-CH4-Thermo ). The two-stage system (R2-H2-Thermo  + R2-CH4-Meso ) achieved the best energetic yield: 5.5 kJ/g COD, which was 41% higher than the single-stage system. Operation of a second-stage reactor at mesophilic temperature is the most suitable for vinasse AD due to its flexibility, robustness, and stability of CH4 production, even in situations of organic overload and accumulation of toxic components. Digestate at ambient temperature is also more adequate for fertirrigation. Graphical abstract: Image 1 Highlights: Two-stage system is superior to single-stage digestion under higher organic load. Single-stage digestion is appropriate for organic load lower than 15 kg COD/m³/d. Thermophilic acidogenesis with mesophilic methanogenesis shows the best performance. 41% higher energy yield by thermophilic + mesophilic system at high organic load. Mesophilic CH4 reactor is more robust and flexible than thermophilic CH4 reactor.